2022
DOI: 10.3389/fimmu.2022.914977
|View full text |Cite
|
Sign up to set email alerts
|

Identification of m6A- and ferroptosis-related lncRNA signature for predicting immune efficacy in hepatocellular carcinoma

Abstract: BackgroundN6-methyladenosine (m6A) methylation and ferroptosis assist long noncoding RNAs (lncRNAs) in promoting immune escape in hepatocellular carcinoma (HCC). However, the predictive value of m6A- and ferroptosis-related lncRNAs (mfrlncRNAs) in terms of immune efficacy remains unknown.MethodA total of 365 HCC patients with complete data from The Cancer Genome Atlas (TCGA) database were used as the training cohort, and half of them were randomly selected as the validation cohort. A total of 161 HCC patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…and our results suggested a higher infiltration rate of resting myeloid DCs in the high-risk group, which may contribute to a poorer immune response. The data from the ESTIMATE method showed that the high-risk group had a higher immune score, which could represent the higher levels of immune cell infiltration in the TME and was consistent with previous studies (58,59). However, our study showed that high risk patients had poor immunotherapy response and high immune cell infiltration levels did not mean a better immunotherapy response.…”
Section: Discussionsupporting
confidence: 91%
“…and our results suggested a higher infiltration rate of resting myeloid DCs in the high-risk group, which may contribute to a poorer immune response. The data from the ESTIMATE method showed that the high-risk group had a higher immune score, which could represent the higher levels of immune cell infiltration in the TME and was consistent with previous studies (58,59). However, our study showed that high risk patients had poor immunotherapy response and high immune cell infiltration levels did not mean a better immunotherapy response.…”
Section: Discussionsupporting
confidence: 91%
“…For example, L et al constructed an m6A-associated lncRNA signature to predict prognosis and immunotherapy of HCC 27 . The results showed that the predictive accuracy of this model was higher than that of other clinical signatures; the value of the model built by Xie et al using lncRNAs based on m6A and ferroptosis co-associated lncRNAs was superior to the former 28 . Thus, we believe that a prognostic model that combines multiple biomarkers is more appropriate.…”
Section: Introductionmentioning
confidence: 81%
“…Although several ferroptosis-associated lncRNAs have been analyzed for their correlation with m6A-related genes in terms of immune efficacy 115 , 116 , 117 , few studies have investigated the specific targets or pathways of m6A and ferroptosis in immune therapy. Given that ferroptosis and m6A play critical roles in tumors, further research on m6A-modified ferroptosis in diverse cancers is needed.…”
Section: The Combination Of M6a and Pcd In Cancersmentioning
confidence: 99%